Another possible risk for the Mediterranean Sea? Aspergillus sydowii discovered in the Port of Genoa (Ligurian Sea, Italy). Issue 1 (15th September 2017) - Greco, G.; Capello, M.; Cecchi, G.; Cutroneo, L.; Di Piazza, S.; Zotti, M.
Abstract: Aspergillus sydowii is a cosmopolitan fungus that has been responsible for the mass destruction of coral in the Caribbean Sea over the last 15 years. To our knowledge, this study has found the first case of A. sydowii in the Mediterranean Sea, in marine-bottom sediments, water and calcareous shells of bivalve molluscs sampled during a campaign to characterise the mycobiota in the Port of Genoa (Italy). The area is characterised by adverse environmental conditions (high turbidity, organic pollution and high concentrations of phosphorus and nitrogen compounds). These parameters, in combination with a rising temperature, could contribute to A. sydowii bloom and dispersal. This fungal strain may have been imported into the Port of Genoa in the bilge water of vessels or by torrent input. This work represents the first step in the implementation of a monitoring programme to safeguard calcareous sponges and sea fan corals endemic in the Mediterranean Sea. Highlights: The first report of Aspergillus sydowii in the Mediterranean Sea We investigated possible transport vehicles of A. sydowii into the Port of Genoa. Possible risk for calcareous sponges and corals endemic in the Mediterranean Sea